2021
DOI: 10.1186/s13073-021-00942-7
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and safety of Bifidobacterium and berberine in human hyperglycemia and their regulatory effect on the gut microbiota: a multi-center, double-blind, randomized, parallel-controlled study

Abstract: Background Berberine and Bifidobacterium have been reported to improve glucose tolerance in people with hyperglycemia or other metabolic disorders. This study aimed to assess the hypoglycemic effect and the regulation of the gut microbiota caused by berberine and Bifidobacterium and the possible additive benefits of their combination. Methods This was an 18-week, multi-center, randomized, double-blind, parallel-controlled study of patients newly di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(58 citation statements)
references
References 54 publications
1
57
0
Order By: Relevance
“…Bifidobacterium is a common gram-positive anaerobic beneficial bacterium, which the stability of relative abundance is crucial for maintaining normal intestinal function and body health. 69 , 70 Studies have shown that the number of Bifidobacterium decreased in UC, and increasing in intestinal tract could alleviate UC. 71–73 However, the present study suggests that the relative abundance of Bifidobacterium did not change over 14 days, but increased significantly by 21 days.…”
Section: Discussionmentioning
confidence: 99%
“…Bifidobacterium is a common gram-positive anaerobic beneficial bacterium, which the stability of relative abundance is crucial for maintaining normal intestinal function and body health. 69 , 70 Studies have shown that the number of Bifidobacterium decreased in UC, and increasing in intestinal tract could alleviate UC. 71–73 However, the present study suggests that the relative abundance of Bifidobacterium did not change over 14 days, but increased significantly by 21 days.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 16 studies met the eligibility criteria with 1,529 participants (n= 761 berberine; 768 = placebo; Table 1; Supplementary file 3 p. 2 shows records for each study). (16-18, 23, 24, 29, 31-40) All studies were conducted in young or middle-aged adults and none of the studies enrolled participants with a history of coronary artery disease or stroke. Thirteen studies (81%) were conducted in mainland China and Hong Kong.…”
Section: Resultsmentioning
confidence: 99%
“…Trial duration ranged from 4 to 24 weeks. Patients enrolled in the studies most frequently had type 2 diabetes mellitus,(23, 24, 32, 35, 39, 40) PCOS,(17, 18, 33, 38) dyslipidemia,(16, 31, 34, 36) or schizophrenia. (29, 37) One study exclusively enrolled men,(16) four studies exclusively enrolled women with PCOS,(17, 18, 33, 38) and the remaining studies enrolled both men and women.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations